Aircraft investment planning and uncertainty - Gibson, William E. (Cranfield University, 2010)
This research sets out to determine whether there is a best way to perform aircraft investment analysis. The question of best practice is found to be linked to corporate ownership: world airline shareholding patterns are identified and linked to investment analysis practices, and to airline financial performance over the last aviation cycle. A key weakness identified by surveying airline practice concerns the treatment of uncertainty in the financial analysis. This research critically examines the state of practice regarding treatment of uncertainties embedded investment valuation assumptions, in airline fleet planning around the world, and proposes structured application of advanced analytical techniques to valuation in today’s world of volatile and diverse aviation markets. The assumptions underlying valuation are embedded in modern financial theory, which has been developed and tested over the last century. The validity and usefulness of financial valuation models is examined from both theoretical and practical perspectives, and the state of practice regarding these models in the airline industry is established, both quantitatively through survey research, and qualitatively through aviation executive interviews in the field. This combined approach has allowed the establishment of ‘paradigms’ characterizing the concrete application of financial theory to the question of aircraft investment. Regional patterns of airline shareholding are identified in a detailed analysis of ownership structure and business models. The resulting governance typology is analyzed in aggregate, and associated with production, and profitability by region. The tendency of each airline ownership type to use modern financial valuation techniques has to some extent been established by applying survey results to the different regions. The fleet planning process and the positioning of investment valuation within it is discussed, and key uncertainties underlying fleet planning assumptions are identified and mapped in a risk map framework. A method for strategic analysis of fleet financing alternatives is derived from classical theory, and applied to the specifics of the aircraft market. The uncertainties surrounding several key modelling assumptions are found to be substantial in the minds of today’s fleet planners, and the assessments of uncertainty vary substantially between airline fleet planners and third-party advisors. The identified practices in applying classical financial theory are found to be strikingly inadequate in treatment of these uncertainties.A model is developed for valuing the acquisition of aircraft under uncertainty, using extensions of the classical financial framework entailing more advanced quantitative techniques. The model’s application to a specific analytical situation analysis show that investment valuations under deterministic models are contradicted when applying uncertainty to key uncertainties present in today’s markets, and a process that yields insights beyond classical finance is proposed.